(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2025)
This scientific study investigates the morphological characteristics of the skin in three-year-old g’o’nons (young horses), specifically focusing on its thickness across different body regions and coat colors. During the study, a total of 140 skin biopsies were collected from 28 anatomical points on the bodies of 5 stallions of varying ages. The thickness of the collected samples was determined both macroscopically using a digital caliper under a magnifying glass and microscopically after preparing histological sections. The results revealed significant variations in skin thickness across different body regions; the thickest skin was recorded at the hoof dermal junction and the dorsal part of the body, while the thinnest skin was observed around the eyes and in the ventral region. Furthermore, black coated g’o’nons were found to have slightly thicker skin compared to their bay and gray-coated counterparts.